The Role of AI in Facilitating Hybrid Work: Implications for Employee Satisfaction and Engagement - Abd. Rasyid Syamsuri; Rifki Arohman; Muhamad Renaldy Saputra; Marcella Angraini (Journal of Global Islamic Economic Studies, 2024)
This study examines the role of artificial intelligence (AI) in facilitating hybrid work arrangements and its implications for employee satisfaction and engagement. The purpose of this research is to analyze how AI-driven systems influence organizational performance and employee experiences within the increasingly prevalent hybrid model of work. Using a literature review method, the study synthesizes findings from journal articles, research reports, and academic books published in recent years, focusing on the integration of AI tools into human resource management and workplace practices. The results indicate that AI enhances efficiency and collaboration by automating routine tasks, supporting decision-making, and enabling data-driven insights that improve resource allocation and employee support. However, the findings also highlight challenges such as algorithmic bias, lack of transparency, and heightened perceptions of surveillance that may undermine trust, satisfaction, and long-term engagement. The discussion emphasizes that the successful implementation of AI in hybrid work requires robust governance, ethical frameworks, and employee participation to ensure fairness and inclusivity. Overall, the study contributes to a deeper understanding of how AI can be strategically leveraged to balance organizational goals with the well-being and dignity of employees, offering both theoretical insights and practical guidance for sustainable HRM practices in the digital era.